The Impact of Mobile Banking Adoption on Financial Inclusion - Mithila, G.; Kengatharan, L.; Fernando, A.M.P. (Shanlax Publications, 2026)
FinTech, especially mobile banking has become a key tool in expanding financial access, particularly in regions underserved by traditional banking. While developed countries focus on improving service use, mobile banking has driven major inclusion gains in emerging and frontier markets by overcoming cost and distance barriers. Despite high banking access in Sri Lanka, usage of digital financial tools remains low, partly due to limited IT literacy which is around 35% and trust concerns. This study examines whether mobile banking awareness, accessibility, digital skills and trust influence financial inclusion using survey data from 220 bank customers in Puttalam district. Statistical analysis is carried out using SPSS 25.0 version and the results show all four factors significantly support inclusion with trust and digital literacy having the strongest effects. The findings suggest mobile banking can effectively promote financial inclusion, but success relies on improving user knowledge, digital skills and confidence in digital systems. The research fills a gap in the frontier market and offers clear direction for policies and FinTech strategies aimed at inclusive financial growth.
Keywords: Financial inclusion; Fin tech; Mobile banking; Frontier markets; Digital literacy; Trust